계절 변화에 따른 립스틱 구매요소가 립스틱 색상 선호도에 미치는 영향 - 정재하(Jae Ha Jeong); 주대원(Deh Won Joo) (한국디자인리서치, 2025)
본 연구는 계절 변화가 립스틱 구매요소 요인과 색상 선호도에 미치는 영향을 분석하는 것을 목적으로 한다. 이를 위해 20대부터 50대까지의 소비자를 대상으로 2024년 10월 31일부터 2025년 1월 13일까지 설문 조사를 실시하였으며, 수집된 데이터를 바탕으로 SPSS를 활용한 빈도 분석, 요인 분석, 신뢰도 분석, 일원분산분석, 다중회귀분석을 수행하였다. 연구 결과, 계절별로 립스틱 색상 선호도에 유의한 차이가 나타났으며, 연령대에 따라 색상 선택 기준과 구매 요인 또한 상이하게 나타났다. 이러한 결과는 계절적 변화가 소비자의 감성 및 색상 선호에 영향을 미친다는 점을 시사하며, 이에 따라 브랜드는 계절별 연령 특성을 고려한 차별화된 마케팅 전략을 수립할 필요가 있음을 제안한다. 본 연구의 결과는 립스틱 브랜드의 효과적인 제품 기획 및 마케팅 전략 수립을 위한 기초 자료로 활용될 수 있다. The purpose of this study is to analyze the impact of seasonal changes on lipstick purchasing factors and color preferences. To achieve this, a survey was conducted from October 31, 2024, to January 13, 2025, targeting consumers in their 20s to 50s. Based on the collected data, frequency analysis, factor analysis, reliability analysis, one-way ANOVA, and multiple regression analysis were performed using SPSS. The results showed significant differences in lipstick color preferences by season, and the criteria for color selection and purchasing factors varied across age groups. These findings suggest that seasonal changes influence consumers' emotions and color preferences. Therefore, brands are advised to develop differentiated marketing strategies that consider seasonal age characteristics. The results of this study can be used as foundational data for effective product planning and marketing strategies for lipstick brands. KCI Citation Count: 0